2012
DOI: 10.22495/cocv9i4c1art4
|View full text |Cite
|
Sign up to set email alerts
|

The impact of good corporate governance practices on financial reporting quality: Empirical evidence from Jordanian listed companies

Abstract: The main objective of this paper is to analyze the relationship between the good corporate governance practices on the financial reporting quality of Jordanian listed companies. Specifically, we focus on the board’s independence, board’s transparency, and separate audit committee. A listing of Share -Traded Jordanian Companies was available from the Amman Stock Exchange as of 31 December 2011. A total of (167) company shares were traded as of 31 of December 2011. It was decided to distribute (160) ques… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
1
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 28 publications
2
1
0
Order By: Relevance
“…[11] found that there is not any significant relationship between family ownership, state ownership, and institutional ownership to the quality of financial statements. Similar findings were also find by [26], [27], and [28] argued that there is a positive relationship between GCG mechanisms measured by the commissioners, audit committees and internal auditors, and the quality of financial statements. In reference to some previous studies, GCG research is focused more on large companies, and it has not been applied on small companies yet, such as cooperatives.…”
Section: Theoretical Framework and Hypothesissupporting
confidence: 85%
“…[11] found that there is not any significant relationship between family ownership, state ownership, and institutional ownership to the quality of financial statements. Similar findings were also find by [26], [27], and [28] argued that there is a positive relationship between GCG mechanisms measured by the commissioners, audit committees and internal auditors, and the quality of financial statements. In reference to some previous studies, GCG research is focused more on large companies, and it has not been applied on small companies yet, such as cooperatives.…”
Section: Theoretical Framework and Hypothesissupporting
confidence: 85%
“…This implies that the larger the size of the audit committee could reduce the value of the firm. This result is in line with Gulzar andWang (2011), Abu-Risheh andAl-Sa'eed (2012), Alfraith and Almutawa (2014), Miko and Kamardin (2015), and Eyenubo, Mohamed and Ali (2017) but inconsistent with Wiralestari & Tanzil (2015) and Majiyebo, Okpanachi, Nyor and Yahaya ( 2018).…”
Section: Regression Analysessupporting
confidence: 58%
“…This is thought to be a factor in the low corporate governance compliance level in the banking industry. This is by the opinion of [22] argue that weak monitoring is the cause of vulnerable application of corporate governance principles.…”
Section: Introductionmentioning
confidence: 99%